2016
DOI: 10.3354/meps11791
|View full text |Cite
|
Sign up to set email alerts
|

Otolith size and the vestibulo-ocular reflex of larvae of white seabass Atractoscion nobilis at high pCO2

Abstract: We investigated vestibular function and otolith size (OS) in larvae of white seabass Atractoscion nobilis exposed to high partial pressure of CO 2 (pCO 2 ) The context for our study is the increasing concentration of CO 2 in seawater that is causing ocean acidification (OA). The utricular otoliths are aragonitic structures in the inner ear of fish that act to detect orientation and acceleration. Stimulation of the utricular otoliths during head movement results in a behavioral response called the vestibulo-ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
1
4
1
Order By: Relevance
“…Despite p CO 2 reportedly having an influence on the otolith morphology of multiple marine teleosts (e.g., Refs. 29 , 30 , 47 , 48 ), environmental p CO 2 (and therefore pH) had no effect on otolith size or polymorph composition in our study. Acid–base regulation is a critical physiological process as inappropriate maintenance will influence the overall performance of the individual by impacting the functionality of proteins and other essential macromolecules 49 .…”
Section: Discussioncontrasting
confidence: 58%
“…Despite p CO 2 reportedly having an influence on the otolith morphology of multiple marine teleosts (e.g., Refs. 29 , 30 , 47 , 48 ), environmental p CO 2 (and therefore pH) had no effect on otolith size or polymorph composition in our study. Acid–base regulation is a critical physiological process as inappropriate maintenance will influence the overall performance of the individual by impacting the functionality of proteins and other essential macromolecules 49 .…”
Section: Discussioncontrasting
confidence: 58%
“…Although there remains no evidence of ocean acidification-induced vaterite replacement in otoliths, including in A. clarkii , there is some evidence for calcite replacement in sagittae and lapilli at elevated pCO 2 (Coll-Lladó et al, 2018); calcite is similarly less dense than aragonite (Nakamura Filho et al, 2014). In terms of kinesthesia, some fish with abnormal and/or asymmetric sagittae/lapilli exhibited kinetoses (Söllner, 2003; Anken, Knie & Hilbig, 2017); however, other studies observed pCO 2 impacts on otolith morphology without observing impacts on behavior (Bignami, Sponaugle & Cowen, 2013; Bignami, Sponaugle & Cowen, 2014; Shen et al, 2016). It is possible the pCO 2 impacts on otolith morphology and asymmetry observed here could impair A. clarkii hearing and kinesthesia, but no sensory or behavioral assays were conducted, so hypotheses remain speculative.…”
Section: Discussionmentioning
confidence: 91%
“…Coupled with functional studies (e.g. [11,48]), this information will help predict whether the inner ear vestibular and auditory sensory systems of fish will be affected by OA. Furthermore, understanding the mechanisms responsible for otolith biomineralization and overgrowth during OA exposure can help improve the accuracy of otolith-reliant aging techniques in the future ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, it was predicted that CO2-induced ocean acidification (OA) would impair otolith biomineralization because the associated decreases in seawater pH and [CO3 2-] hamper CaCO3 precipitation [9]. However, subsequent studies reported that fish exposed to OA developed enlarged otoliths [10][11][12][13][14][15][16]. These findings led to a broader awareness otolith biomineralization is strongly linked to endolymph and blood chemistries, and to the hypothesis that biological regulation of endolymph pH could lead to increased [CO3 2-] resulting in otolith overgrowth [10].…”
Section: Introductionmentioning
confidence: 99%